Constructing directed strongly regular graphs by using semidirect products and semidihedral groups - Pi̇ri̇, Semih; Olmez, Oktay; Şahi̇n, Murat (Communications Faculty of Sciences University of Ankara Series A1 Mathematics and Statistics, 2023)
In this paper, directed strongly regular graphs (DSRGs) are constructed by using semidirect products. The orbit condition in [3] has been weakened and this gives rise to the construction of DSRGs. Moreover, a different construction is given for DSRG by using semidihedral groups.
Keywords: Matematik; Directed strongly regular graphs; semidirect products; semidihedral groups; Cayley graphs; Mathematical Sciences